2001
DOI: 10.1016/s0896-6273(01)00395-6
|View full text |Cite
|
Sign up to set email alerts
|

Activated Notch2 Signaling Inhibits Differentiation of Cerebellar Granule Neuron Precursors by Maintaining Proliferation

Abstract: In the developing cerebellar cortex, granule neuron precursors (GNPs) proliferate and commence differentiation in a superficial zone, the external granule layer (EGL). The molecular basis of the transition from proliferating precursors to immature differentiating neurons remains unknown. Notch signaling is an evolutionarily conserved pathway regulating the differentiation of precursor cells of many lineages. Notch2 is specifically expressed in proliferating GNPs in the EGL. Treatment of GNPs with soluble Notch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
249
2
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(264 citation statements)
references
References 51 publications
11
249
2
2
Order By: Relevance
“…Notch 2 basal expression at P5 was most prominent in less mature areas of the OE, where neurogenesis is still proceeding, and fewer cell layers are occupied by Dcx-or NST-positive immature neurons. Notch 2 expression in neuronal precursors has also been detected in the external granule layer of the cerebellum (Solecki et al, 2001), where it correlated with expression of Hes-1. In addition, we found a novel Notch 2 expression pattern in some Sus4-positive sustentacular cells, both actively cycling and PCNA-negative (Fig.…”
Section: Embryonic and Postnatal Neuronal Progenitors And Adult Sustmentioning
confidence: 95%
See 1 more Smart Citation
“…Notch 2 basal expression at P5 was most prominent in less mature areas of the OE, where neurogenesis is still proceeding, and fewer cell layers are occupied by Dcx-or NST-positive immature neurons. Notch 2 expression in neuronal precursors has also been detected in the external granule layer of the cerebellum (Solecki et al, 2001), where it correlated with expression of Hes-1. In addition, we found a novel Notch 2 expression pattern in some Sus4-positive sustentacular cells, both actively cycling and PCNA-negative (Fig.…”
Section: Embryonic and Postnatal Neuronal Progenitors And Adult Sustmentioning
confidence: 95%
“…The Notch regulator, Numb, has also been detected in the SVZ, where it is asymmetrically located to the apical membrane of progenitors and contributes to their maintenance (Zhong et al, 1996(Zhong et al, , 2000Petersen et al, 2002Petersen et al, , 2004. Notch 2 is found in cerebellar granule neuron precursors, where it prolongs proliferation when overexpressed in activated form, suggesting that it may also contribute to progenitor maintenance (Solecki et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…3,34 For example, the Hatton group has shown that Notch signaling maintains CGNP proliferation, and that SHH treatment of CGNPs induces expression of the Notch effector Hes1. 35 To investigate miRNAs negatively regulating the NOTCH pathway in the context of medulloblastomas, Garzia et al recently performed an in-silico analysis of miRBase to identify miRNAs predicted percentage of human medulloblastomas (~60%; Fig. 1).…”
Section: Mir-17/92 In Medulloblastoma Pathogenesismentioning
confidence: 99%
“…Indeed, D1-cyclin has been shown to be upregulated by Notch signaling, 34 known to inhibit differentiation of cerebellar granule neuron precursors by maintaining proliferation. 35 Abnormally elevated levels of CCND1 in cerebellar granule neuron precursors, by disrupting proliferation/ differentiation processes in these cells, might have impaired cerebellar development in our patients. In this context, the surprisingly elevated levels of ZNF592, CCND1 and CCND2 transcripts in the heterozygous father ( Supplementary Figure 2), are difficult to interpret, but might be explained by the fact that the regulation of the described pathways is highly orchestrated in time, and that the amount of each TF might change rapidly in time, with a combination of tightly regulated levels of expression.…”
Section: Resultsmentioning
confidence: 82%